Yield and Postharvest Quality of Glutinous Corn (Zea Mays L.) in Response to Bio-Pesticides and Plastic Mulch Applied - Galon, Francis (Journal of Interdisciplinary Perspectives, 2025)
This study evaluated the effects of corn variety, plastic mulch application, and different bio-pesticide combinations on the yield and postharvest quality of glutinous corn (Zea mays L.) under wet and dry season conditions. Two varieties, Klasika and Sweet Purple, were tested along with treatments involving plastic mulch and four bio-pesticide combinations. Results showed that Klasika consistently produced longer and heavier ears with higher yields compared to Sweet Purple, although differences in some parameters were not statistically significant. Dry season planting resulted in significantly better performance across most measured traits, including ear weight, yield, and insect damage, compared to the wet season, which was characterized by unfavorable weather conditions such as typhoons. Plastic mulch negatively affected ear production and increased insect damage during the wet season but had minimal impact during the dry season. Among bio-pesticide treatments, simpler applications of crop vaccine or bio-pesticide alone generally outperformed combinations with micronutrients, leading to higher yields and better postharvest quality, such as total soluble solids and shelf life. The study suggests that selecting the Klasika variety, planting during the dry season, and using simpler bio-pesticide treatments without plastic mulch during the wet season can optimize glutinous corn production and quality. These findings provide valuable guidance for farmers and stakeholders aiming to improve corn productivity while managing costs and environmental conditions effectively.